2021
DOI: 10.3390/toxins13110751
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Neurotoxins in Central Nervous System: An Overview from Animal Models to Human Therapy

Abstract: Botulinum neurotoxins (BoNTs) are potent inhibitors of synaptic vesicle fusion and transmitter release. The natural target of BoNTs is the peripheral neuromuscular junction (NMJ) where, by blocking the release of acetylcholine (ACh), they functionally denervate muscles and alter muscle tone. This leads them to be an excellent drug for the therapy of muscle hyperactivity disorders, such as dystonia, spasticity, and many other movement disorders. BoNTs are also effective in inhibiting both the release of ACh at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 141 publications
(159 reference statements)
1
24
0
Order By: Relevance
“…Except for peripheral mechanisms, we also explored the central mechanisms of perineural injection of BoNT/A-induced analgesia. It is well established that indirect central effects can be produced by peripherally injected BoNT/A through peripheral mechanisms of alteration of central sensorimotor integration [31]. Therefore, the results associated with peripheral protective effects of BoNT/A in this study suggested the indirect central effect of perineural injection of BoNT/A.…”
Section: Discussionsupporting
confidence: 56%
“…Except for peripheral mechanisms, we also explored the central mechanisms of perineural injection of BoNT/A-induced analgesia. It is well established that indirect central effects can be produced by peripherally injected BoNT/A through peripheral mechanisms of alteration of central sensorimotor integration [31]. Therefore, the results associated with peripheral protective effects of BoNT/A in this study suggested the indirect central effect of perineural injection of BoNT/A.…”
Section: Discussionsupporting
confidence: 56%
“…In all the studies presented thus far, the exact mechanism by which the peripherally injected BoNT/A reaches the spinal cord, where it may block both neuronal synaptic release and spinal glial activation, is not yet completely understood. As has been suggested in many studies that have used animal models [ 68 ], a direct central effect of the peripheral administration of BoNT/A is conceivable as a consequence of its retrograde transport along the axons of sensory neurons and its subsequent transcytosis to neuronal and non-neuronal spinal cells, where it can block both the release of neurotransmitters and the activation of spinal glia cells. It should be noted that, although the retrograde transport of the toxin can be evoked as a mechanism by which the peripheral toxin can reach the spinal cord in animal models, for obvious reasons, it is desirable that this does not happen in humans.…”
Section: Interactions Between Bonts Microglia and Astrocytesmentioning
confidence: 99%
“…The central effects of BoNTs, following their peripheral administration, have been the subject of debate in the literature, and a consensus has not yet been reached as to their direct or indirect effects [ 190 , 191 , 192 ]. A 2018 review by Caleo and Restani [ 191 ] summarizes studies that have so far provided evidence of the retrograde transport of BoNTA after its peripheral injection and that this process might contribute to the clinical effects of BoNTA through a direct action on the central circuits [ 191 ].…”
Section: Mechanisms Underlying the Antipruritic Effect Of Bontsmentioning
confidence: 99%